2017
DOI: 10.7150/thno.18833
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Tissue-Engineered Bionic Urethra Using Cell Sheet Technology and Labeling By Ultrasmall Superparamagnetic Iron Oxide for Full-Thickness Urethral Reconstruction

Abstract: Urethral strictures remain a reconstructive challenge, due to less than satisfactory outcomes and high incidence of stricture recurrence. An “ideal” urethral reconstruction should establish similar architecture and function as the original urethral wall. We fabricated a novel tissue-engineered bionic urethras using cell sheet technology and report their viability in a canine model. Small amounts of oral and adipose tissues were harvested, and adipose-derived stem cells, oral mucosal epithelial cells, and oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 58 publications
(56 reference statements)
0
38
0
Order By: Relevance
“…Oral mucosal epithelial cells were harvested from canine oral mucosal epithelium and prepared as reported previously [19]. Oral mucosal epithelial cells were obtained from the buccal mucosa of beagle dogs.…”
Section: Methodsmentioning
confidence: 99%
“…Oral mucosal epithelial cells were harvested from canine oral mucosal epithelium and prepared as reported previously [19]. Oral mucosal epithelial cells were obtained from the buccal mucosa of beagle dogs.…”
Section: Methodsmentioning
confidence: 99%
“…Some animal studies indicated that BM-EPC cell sheet technology increased vasculogenesis [12]. However, BM-EPCs cell sheet can not harvested with trypsin and cell-to-cell interactions and the integral structure of the BM-EPCs sheet were unknown [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Cell sheets have been widely used to repair defects with the development of tissue engineering (Joseph et al, 2006). Compared to scaffold and traditional cells composition, cell sheets feature uniform distribution of cells and complete ECM 3-dimensional structure (Zhou et al, 2017). BMSCs are dominant cells in the process of osseointegration and have advantages of accessibility, multiple differentiation potential, and immune-evasion.…”
Section: Discussionmentioning
confidence: 99%